Lean body mass, fat body mass, dan indeks massa tubuh terhadap tekanan darah mahasiswa - Nachrisya Hazna Fathia; Neni Trilusiana Rahmawati; Ch. Tri Nuryana (Faculty of Medicine, Public Health, and Nursing Universitas Gadjah Mada, 2024)
The relationship of lean body mass, fat body mass, and body mass index with blood pressure in studentsBackground: Hypertension shows a significant upward trend in prevalence globally and nationally. This phenomenon is also observed among young adults, including university students, due to unhealthy lifestyle transitions. Although body mass index (BMI) is commonly used as a risk factor indicator, it has limitations in distinguishing between lean body mass (LBM) and fat body mass (FBM).Objective: This study aimed to analyze the relationships of LBM, FBM, and BMI with blood pressure among Universitas Gadjah Mada (UGM) students. Methods: This was an analytic observational study with a cross-sectional design involving 124 UGM students selected through purposive sampling. Anthropometric measurements were performed according to the International Society for the Advancement of Kinanthropometry (ISAK) standards. LBM was estimated using the Boer formula, FBM using the Durnin & Womersley equation, BMI using the weight-to-height squared equation, and systolic and diastolic blood pressure were measured with a sphygmomanometer. Data analysis was conducted using Pearson and Spearman correlation tests. Results: LBM showed a significant positive correlation with systolic blood pressure (r=0.624; p<0.001) and diastolic blood pressure (r=0.316; p<0.001). BMI also showed a significant positive correlation with both blood pressure components (p<0.001), whereas FBM was significant only for diastolic blood pressure (r=0.266; p=0.003). Correlation analysis stratified by gender revealed specific patterns: in males, LBM and BMI were significantly positively associated only with diastolic blood pressure, whereas in females, FBM was consistently and significantly positively associated with both systolic and diastolic blood pressure. Conclusions: There is a significant positive relationship between LBM, FBM, and BMI with blood pressure in university students.